Traditional Game-Based Basic Movement Learning Model for Elementary School Children - Alpen, Joni; Apriani , Leni; Azmi , Muhammad; Hanema, Vanny (Indonesian Journal of Sport Management, 2024)
In this research, this era of very sophisticated and developing technology has influenced all aspects of life in various fields, including education. This technological progress is something that cannot be avoided in everyday life. Gadgets are part of the development of technology, which were initially a means of communicating using a landline telephone but have now become mobile phones, both Android and iOS. Especially elementary school children whose developmental age at school determines their development. This research method uses the development of the Thiagarajan model. This model is a learning tool development that explains in detail the operational steps for developing the tool. The population and sample for this research were 2 elementary schools. Based on the results of the previous study and discussion, research into basic movement learning models based on traditional games for elementary school children has produced 15 model items. Traditional game-based basic movement learning for elementary school children has been proven effective and is highly used in improving elementary school children's basic movements.